Psychological wellbeing among teachers in Malaysia: the relationship between burnout, resilience and school factor - Mat Zin, Nur Izzati; Sulong, Rose Manisah; Nor Zainudin, Zaida (Human Resource Management Academic Research Society, 2024)
Teaching career is one of the professions that experiences high levels of mental pressure. This study aims to examine the teacher’s burnout, the teacher’s resilience, school culture, and the psychological well-being among school teachers in Malaysia. This study also investigates differences in gender, location of schools, and the marital status of teachers that influence the teacher’s psychological wellbeing. Factors that contribute to the psychological well-being among school teachers in Malaysia are also examined. The research utilizes a quantitative method with a correlational framework encompassing a combined count of 320 teachers randomly chosen from various regions of Malaysia. The instruments used for this study include Ryff’s Psychological Well-Being Scale, Teacher’s burnout scale, Teacher Resilience Scale, and Positive School Culture Scale. The data were analyzed by using SPSS software, involving descriptive and inferential analysis. The findings indicate that resilience and school culture are related to the psychological well-being among teachers in Malaysia. However, only the resilience is identified as a factor affecting the well-being of teachers in Malaysia. It is hoped that this study can serve as a guide for specific departments such as school administrators in planning and implementing intervention programs to enhance resilience and psychological well-being among teachers in Malaysia.